MODERN DIRECTIONS OF HERPESVIRUS INFECTIONS PHARMACOTHERAPY - Lyadova, T. I.; Volobuyeva, О. V.; Savvo, А. N.; Sanina, К. S.; Malanchuck, S. G. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2015)
The article presents the data on the etiology, pathogenesis, clinical course, features of an immune response to human herpesvirus infections. Modern approaches to the causal treatment and principles of treatment phasing in these patients category are discussed.